- دور الصكوك الوقفية في تحقيق التنمية المستدامة" - تجارب دولية" - رمضاني, مروى; بوقرة, كريمة; ساعد بخوش, حسينة (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى إبراز الدور الذي تلعبه الصكوك الوقفية في تحقيق التنمية المستدامة بإعتبارها صيغة تمويلية مستحدثة في جذب الموارد المالية وإستثمارها، وقد تم التطرق إلى تجارب بعض الدول في إصدار الصكوك الوقفية، حيث تم التوصل إلى أن الدول التي قامت بتبني العمل بالصكوك الوقفية إستطاعت تحقيق نجاح كبير في إقامة مشاريعها الإستثمارية، وأن دولة ماليزيا تعتبر النموذج الناجح دوليا في تحقيق التنمية المستدامة. This study aimed to highlight the role that endowment instruments play in achieving sustainable development, considering that it is an innovative financing formula in attracting financial resources and investing them. The experiences of some countries in issuing endowment instruments have been addressed, and it was concluded that the countries that adopted the work of the endowment instruments were able to achieve great success in establishing its investment projects, and that Malaysia is considered an internationally successful model in achieving sustainable development
"The Role of Endowment Instruments in Achieving Sustainable Development" - International Experiences -
مقال
Keywords: الوقف ; الصكوك الوقفية ; التنمية ; الإستدامة ; التنمية المستدامة; endowment ; endowment instruments ; development ; sustainability ; sustainable development